Orbicularis oculi reflex in coma: clinical, electrophysiological, and pathological correlations - Lyon, Lynn W. (1972)
The orbicularis oculi reflex was studied in 48 comatose patients and the results were correlated with clinical and pathological findings. The late component of the reflex was absent or of minimal amplitude in all cases regardless of the site of lesions, reflecting a diffuse suppression of the reticular system rather than a specific or local block in the brain-stem. Alteration of the early component of the reflex, on the other hand, generally indicated primary or secondary structural changes in the pons, although reversible functional or pharmacological block of pontine conduction was also documented.